An Empirical Study of Training End-to-End Vision-and-Language Transformers - Dou, Zi-Yi; Xu, Yichong; Gan, Zhe; Wang, Jianfeng; Wang, Shuohang; Wang, Lijuan; Zhu, Chenguang; Peng, Nanyun (Violet); Liu, Zicheng; Zeng, Michael (CVPR, 2022)
Vision-and-language (VL) pre-training has proven to be highly effective on various VL downstream tasks. While recent work has shown that fully transformer-based VL models can be more efficient than previous region-feature-based methods, their performance on downstream tasks are often degraded significantly. In this paper, we present METER (Multimodal End-to-end TransformER), through which we systematically investigate how to design and pre-train a fully transformer-based VL model in an end-to-end manner. Specifically, we dissect the model designs along multiple dimensions: vision encoders (e.g., CLIP-ViT, Swin transformer), text encoders (e.g., RoBERTa, DeBERTa), multimodal fusion (e.g., merged attention vs. co-attention), architecture design (e.g., encoder-only vs. encoder-decoder), and pre-training objectives (e.g., masked image modeling). We conduct comprehensive experiments on a wide range of VL tasks, and provide insights on how to train a performant VL transformer while maintaining fast inference speed. Notably, METER achieves an accuracy of 77.64% on the VQAv2 test-std set using only 4M images for pre-training, surpassing the state-of-the-art region-feature-based VinVL model by +1.04%, and outperforming the previous best fully transformer-based ALBEF model by +1.6%.